Identifying the mechanism underlying treatment failure for Salmonella Paratyphi A infection using next-generation sequencing – a case report - Hye-Ran Park; Dong-Min Kim; Na-Ra Yun; Choon-Mee Kim (BMC Infectious Diseases, 2019)
Abstract Background Salmonella is a notorious pathogen that causes gastroenteritis in humans and the emergence of resistance to third-generation cephalosporins and azithromycin have raised concern. There has been rare case of Salmonella Paratyphi A infection accompanied by spondylitis. Here, we report a case of initial antibiotic treatment failure in a Korean man with Salmonella Paratyphi A infection and conducted next-generation sequencing (NGS) to determine the cause of failure of initial treatment for Salmonella Paratyphi A infection. Case presentation A 70-year-old man was admitted to Chosun University Hospital with reported consistent low back pain with a history of having 5 days of chills and fever in another hospital a month ago. He was administered ceftriaxone (2 g daily) for 18 days including initial treatment to cover Salmonella enterica. The antimicrobial susceptibility test using MIC plate, found that the identified organism was resistant to ciprofloxacin and nalidixic acid. Moreover, the Salmonella Paratyphi A isolates were found to have an MIC > 16 mg/L for azithromycin, as he had resistance to both azithromycin and nalidixic acid, the treatment was switched to a combination of ciprofloxacin and cefotaxime. We carried out next-generation sequencing (NGS) to determine the cause of failure of initial treatment for Salmonella Paratyphi A infection. NGS showed that the amino acid substitution GyrA S83F and the expression of multiple RNA-family efflux pumps led to a high-level resistance to quinolone. No genes related to ceftriaxone resistance, such as CTX-M, CMY-2, or other extended-spectrum beta-lactamases were identified in Salmonella enterica Paratyphi A using NGS. The GyrA S83F mutation and the expression of multiple RNA-family efflux pumps may have contributed to the treatment failure of ceftriaxone, even though the MIC of the isolate to ceftriaxone was less than 1. Conclusion This case involved a Salmonella Paratyphi A infection accompanied by spondylitis. To our knowledge, this is the first report to elucidate the mechanism underlying antimicrobial resistance using NGS.